Analisis Kebugaran Jasmani Siswa Ditinjau Dari Keikutsertaan Ekstrakurikuler Olahraga Di SMP Islam Nudia Semarang - Wisnu Maula Wardana; Wahyu Ragil Kurniawan; Cahyo Yuwono; Dwi Gansar Santi Wijayanti (Universitas Negeri Semarang, 2024)
Extracurricular activities as additional activities outside of learning hours have not been carried outso that extracurricular participants do not know the benefits and achievement of goals in thecomponents and functions of physical fitness. This type of research is a quantitative descriptive surveywith observation, tests, and documentation as data collection techniques. The population andresearch sample were all extracurricular sports participants at Nudia Islam Junior High School. Theresults showed that the level of physical fitness was classified as sufficient with an average value of17.6; the level of physical fitness of extracurricular futsal at junior high school was classified as goodwith an average value of 18.7; the level of physical fitness of pencak silat extracurricular at NudiaIslamic Junior High School was classified as sufficient with an average value of 16.5. Students'physical fitness has not reached the standard of good physical fitness condition